2016
DOI: 10.1016/j.jelechem.2016.03.007
|View full text |Cite
|
Sign up to set email alerts
|

SECM screening of the catalytic activities of AuPd bimetallic patterns fabricated by electrochemical wet-stamping technique

Abstract: a b s t r a c tElectrocatalyst arrays with various AuPd compositions have been deposited onto an indium tin oxide (ITO) surface by an electrochemical wet-stamping (EWETS) technique. Micropatterned high-strength agarose containing different solutions of chloroauric acid and chloropalladic acid has been used to electrodeposit and generate patterns of AuPd nanoparticle arrays on ITO. The compositions of the AuPd catalysts prepared by EWETS have been determined through a combination of energy-dispersive X-ray anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…The Pt NPs were better resolved than those shown in Figure a because of the closer tip distance . SECM was applied to screen Ag NPs for the electrocatalytic degradation of CHCl 3 . The electrochemical activities of AuPd alloys for H 2 O 2 and FcMeOH + reduction reactions have been investigated in both redox-competition and FB modes .…”
Section: Scanning Electrochemical Microscopymentioning
confidence: 99%
See 1 more Smart Citation
“…The Pt NPs were better resolved than those shown in Figure a because of the closer tip distance . SECM was applied to screen Ag NPs for the electrocatalytic degradation of CHCl 3 . The electrochemical activities of AuPd alloys for H 2 O 2 and FcMeOH + reduction reactions have been investigated in both redox-competition and FB modes .…”
Section: Scanning Electrochemical Microscopymentioning
confidence: 99%
“…SECM was applied to screen Ag NPs for the electrocatalytic degradation of CHCl 3 . The electrochemical activities of AuPd alloys for H 2 O 2 and FcMeOH + reduction reactions have been investigated in both redox-competition and FB modes . Scanning droplet cell microscopy (SDCM) was used to characterize various materials, including organic semiconductors, Ce-rich OER catalysts, and solar fuel photoanodes in CuO-V 2 O 5 .…”
Section: Scanning Electrochemical Microscopymentioning
confidence: 99%
“… 546 The RC and SG-TC modes were also applied to investigate the electrochemical activities of various AuPd compositions deposited onto ITO toward H 2 O 2 and FcMeOH + reduction reactions. 547 Tomlinson et al reported the first use of electrochemical imaging to identify the defect and defect-free areas in single crystal boron-doped diamond (BDD) electrodes. Intermittent contact SG-TC-SECM was successfully used to detect defects in single crystal BDD electrodes by measuring variations in the tip current in correlation with changes in the boron dopant levels in the materials.…”
Section: Operando Sepm Applications In Electrocatalysismentioning
confidence: 99%
“…A Au surface was biased to generate H 2 O 2 while the selective tip was employed for imaging the distribution of H 2 O 2 . The RC and SG-TC modes were also applied to investigate the electrochemical activities of various AuPd compositions deposited onto ITO toward H 2 O 2 and FcMeOH + reduction reactions . Tomlinson et al reported the first use of electrochemical imaging to identify the defect and defect-free areas in single crystal boron-doped diamond (BDD) electrodes.…”
Section: Operando Sepm Applications In Electrocatalysismentioning
confidence: 99%
“…Before statistically analyzing the retrieved articles, their abstract, title, and keywords were manually screened to detect and remove any irrelevant ones. For instance, the keyword "multicomponent alloy*" retrieved many articles, such as [47][48][49][50][51][52], which did not belong to the field of HEA. Eventually, 3541 research articles were retrieved and analyzed.…”
Section: Text Cleaningmentioning
confidence: 99%